1949
DOI: 10.1021/ie50479a028
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Dusts and Fumes in the Los Angeles Area

Abstract: Meteorological and topographical conditions in the LosAngeles basin cause the retention of dusts and fumes, frequently for several days. Eye irritation and limited visibility are characteristic of the resultant smog. Studies of the aerosols in this area have been undertaken by government and private laboratories. Methods and equipment used by the Los Angeles County Air Pollution Control District in identification of industrial contaminants are described. The roles of sulfuric acid mist and metallurgical dusts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1950
1950
1954
1954

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Fog is not a necessary component of the smog ; in fact, more often than not, it is absent. Smog is generally distributed in urban and industrial areas, but economic plant damage due to smog has been reported only in the Los Angeles area, where, owing to the recent greatly increased industrialization, together with the low wind velocities of summer and autumn and large-scale, semi-permanent, non-diurnal temperature inversions (86), the industrial and urban wastes discharged into the atmos phere can sometimes reach concentrations sufficient to cause injury to vege tation (24, p. 148 ; 46, 82a, 83, 87). The injury has economic significance only in "heavy" smog when the inversion layer and the wind velocity are low and the concentration of the toxicants is raised materially above the us ual "smog" level.…”
Section: Mercury Vapormentioning
confidence: 99%
See 1 more Smart Citation
“…Fog is not a necessary component of the smog ; in fact, more often than not, it is absent. Smog is generally distributed in urban and industrial areas, but economic plant damage due to smog has been reported only in the Los Angeles area, where, owing to the recent greatly increased industrialization, together with the low wind velocities of summer and autumn and large-scale, semi-permanent, non-diurnal temperature inversions (86), the industrial and urban wastes discharged into the atmos phere can sometimes reach concentrations sufficient to cause injury to vege tation (24, p. 148 ; 46, 82a, 83, 87). The injury has economic significance only in "heavy" smog when the inversion layer and the wind velocity are low and the concentration of the toxicants is raised materially above the us ual "smog" level.…”
Section: Mercury Vapormentioning
confidence: 99%
“…Swain (28) has reviewed the outstanding periodic developments of this century. The Donora incident (18) of October 1948, coupled with the investigation of atmospheric pollution which was already in progress at that time in the Los Angeles area (84,85,86,88,89) and a rather widespread concern over fluorine emanations, has resulted in another period of heightened interest in this subject and many new studies are being made and published cur· rently. Also, a number of reviews of older work (13; 24, pp.…”
mentioning
confidence: 99%
“…The Pittsburgh, Pa., region has contributed to the atmosphere much soot from coal combustion and metallic oxides from iron and zinc production (7). The Los Angeles region, where coal consumption and smoke are relatively unimportant, contributes dusts, fumes, and liquid aerosols predominantly on heavy smog days (9). Atmospheric pollutants may comprise aerosols which have undergone spontaneous modification or modification by the chemical and physical conditions of the atmosphere, as well as unmodified aerosols.…”
Section: Surface Dirt Formationmentioning
confidence: 99%
“…McCabe and coworkers (9) reported that solid particles are capable of acting as nuclei of hygroscopic aerosols and these particles, as well as atmospheric and toxic gases such as sulfur dioxide, tend to dissolve in the condensed moisture. Johnstone (5,9) pointed out that an increase in relative humidity causes an increase in the particle size of a hygroscopic aerosol and stabilizes the aerosol. Chemical reactions may occur between the component parts of an aerosol or between the aerosol and the atmosphere.…”
Section: Surface Dirt Formationmentioning
confidence: 99%
See 1 more Smart Citation